(untitled) (Veterinary Science, 2017)
The present research analizes agricultural and livestock farms behaviour in pampa arenosa during during 1984-1988 and 1991- 1995 periods, comparing structure and economic results of those farms before and after open economic and convertibility law. Hundred and eleven farms samples of the westem sandy were considered. Anova (variance analysis) and Multiple Regression technics were used to show structgral differences in the first case and profits variations in the second one Results show the modifications in productive structure, agnculture area increase and intensificating product-land relation. This new resources allocation, according to economic policies, has supposed an increased productir-e result by ha. Accaunting for 172,85 % measured into USA dollar betn.een both periods